Pengaruh Cyber Religion Marketing dalam TikTok @am.event terhadap Minat Beli Tiket Pengajian Agama Ustadz Hanan Attaki. - Nur Fadhilah, Dila; Herma Retno Prabayanti (Universitas Negeri Surabaya, 2025)
In this digitalization era, social media has become a key medium for disseminating religious messages and marketing activities. The phenomenon of cyber religion utilizes digital platforms like TikTok to distribute religious content widely, while cyber marketing offers an interactive approach that attracts audience attention, particularly generation Z as active social media users. This study aims to analyze the influence of cyber religion marketing conducted by Ayah Amanah event organizer through its TikTok account @am.event on the purchase intention of tickets for Ustadz Hanan Attaki's religious lectures. This research employs a quantitative method by distributing online questionnaires to 100 generation Z respondents, who are followers of the @am.event TikTok account. The linear regression test results show a significant influence with a significance value of 0.00 < 0.05. The hypothesis test reveals that the t-value (8.388) is greater than the t-table value (1.984), meaning Ha is accepted and H0 is rejected. Thus, cyber religion marketing through TikTok @am.event significantly influences the purchase intention for Ustadz Hanan Attaki's religious lecture tickets.